Development of rational model for Lithuanian construction industry/Lietuvos racionalios statybos šakos modelio kūrimas - Zavadskas, Edmundas K.; Rutkauskas, Aleksandras V. (Journal of Civil Engineering and Management, 1999)
By modelling and forecasting future perspectives and trends of the construction industry, it is possible to get prepared in advance to respond to the changes of macro- and microlevel variables (eg enterprise restructuring and structural change, sources of company finance, information system of construction, financial sector, interest rate, inflation, innovation, etc) which affect the Lithuanian economy. The lifetime process model suggested by this research is based on the presumption that the efficiency of the construction industry depends on many micro- and macrolevel variables. The presence of specific macro- and microlevel variable factors immediately imposes objective limitations for the efficient use of the resources of the construction industry. The construction industry, in the presence of these limitations, performs its functions within these constraints as efficiently as possible. For instance, construction organisations, being influenced by particular macro- and microlevel environment variables, would do their best to undertake the activities within restricted aspects of the construction industry (eg designing, production of building materials, construction of dwellings, thermal refurbishment of buildings, etc), geographic locations, and with such interested parties, where the goals of all parties would find maximum satisfaction. Organisations which base themselves on this assertion, try to create a rational environment and operating conditions to achieve the best satisfaction of their customers' needs, to win a better reputation and to earn more profit. Therefore, based on the main development trends of the construction industry (in advanced industrial economies), it is possible to develop recommendations on how to increase the efficiency of the transitional construction industry in Lithuania. This research seeks to produce a model of the rational construction industry in Lithuania by undertaking a complex analysis of micro- and macroenvironment factors affecting it and to give recommendations on the increase of its competitive ability. Simulation modelling was undertaken to provide insight into how to create an effective environment for the construction industry by choosing rational micro- and macrofactors. This research seeks to explore ways of harmonising the relationship between the transitional Lithuanian construction and its environment. The research outlines the changing nature of the Lithuanian transitional construction economy, examines the effect of the changing external environment on the efficiency of the construction industry, proposes a theoretical model representing the current situation in Lithuania and presents a model for an efficient environment in the Lithuanian construction industry. While the construction organisations cannot alter the micro- and macrolevel variables, they can assess their impact and take them into consideration when realising projects. Organisations, being aware of the micro- and macrolevel factors which affect the projects being realised, should be able to organise their present and future activities more successfully.Article in Lithuanian.First Published Online: 26 Jul 2012